Conference on Lasers and Electro-Optics 2012 2012
DOI: 10.1364/cleo_at.2012.cthc5.4
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Three-Photon Microscopy of Subcortical Structures within an Intact Mouse Brain

Abstract: Two-photon fluorescence microscopy (2PM) 1 enables scientists in various fields including neuroscience 2,3 , embryology 4 , and oncology 5 to visualize in vivo and ex vivo tissue morphology and physiology at a cellular level deep within scattering tissue. However, tissue scattering limits the maximum imaging depth of 2PM within the mouse brain to the cortical layer, and imaging subcortical structures currently requires the removal of overlying brain tissue 3 or the insertion of optical probes 6,7 . Here we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
292
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(295 citation statements)
references
References 0 publications
2
292
0
1
Order By: Relevance
“…Here, we demonstrate a simple way to reduce the excitation volume along the axial direction by utilizing three-photon excitation fluorescence (3PEF) with TF microscopy (3PEF-TF). The cubic dependence of the 3PEF signal on the excitation intensity allows the excitation volume in TF microscopy to be further confined in a similar manner to point-scanning 3PEF microscopy [12]. Third harmonic generation, the intensity of which is proportional to the cubic of the excitation intensity, has been applied to TF microscopy with line illumination [13].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate a simple way to reduce the excitation volume along the axial direction by utilizing three-photon excitation fluorescence (3PEF) with TF microscopy (3PEF-TF). The cubic dependence of the 3PEF signal on the excitation intensity allows the excitation volume in TF microscopy to be further confined in a similar manner to point-scanning 3PEF microscopy [12]. Third harmonic generation, the intensity of which is proportional to the cubic of the excitation intensity, has been applied to TF microscopy with line illumination [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that by relying on such higher order nonlinear process, fluorescence is confined to a smaller volume, reducing out-of-focus light. 17,22 Novel laser sources have recently been developed to generate high energy pulses to optimize the absorption of three photons. Such ultrashort Compressive sensing is demonstrated a posteriori, by using 5% and 15% of the recorded Hadamard patterns and minimizing to the l1 norm.…”
Section: Three-photon Trafixmentioning
confidence: 99%
“…pulsed lasers typically have pulse duration and repetition rate below 70 fs and 1.25 MHz, [17][18][19][20][21]23 respectively. The Ti:Sapphire laser source in our system is typically used to generate 2P excitation, therefore, it is not optimal for 3P microscopy.…”
Section: Three-photon Trafixmentioning
confidence: 99%
“…Since its first demonstration, nonlinear light microscopy (NLM), including multi-photon fluorescence microscopy [1][2][3][4][5][6] and multi-harmonic generation microscopy [7][8][9], has attracted much biological and medical interest due to its capability to provide molecular and structural information with high 3D spatial resolutions. Recently, enabled by femtosecond near-infrared (NIR) solid-state light sources working in the 0.7-1.3 μm bio-penetration window, NLM with a solid-state NIR light source offers the advantages of deeper penetration and much reduced photodamage and photobleaching effects [2,4,8].…”
Section: Introductionmentioning
confidence: 99%